Liberal World Order and Global Security Governance: Analyzing Its Impact On the Global South Through a Case Study of Afghanistan - Muhammad Saeed (ASIAN Journal of International Peace & Security (AJIPS), 2024)
This article attempts to understand the nature of global security governance in the context of relations between the West and the global South under liberal world order. To do this, it asks a simple question: what the global security governance seeks to secure and from whom and what to secure? Focusing on these question, this study engages critically with theory and practice of liberal internationalism. This critique is informed by insights from critical theory of Rober W. Cox, post-structural theory of Markus Kienscherf and postcolonial theory of Alexander D. Barder. This study is mainly qualitative and analytical. Besides secondary sources such as books, research reports and articles etc., primary sources such as declassified documents of United States government available online, as well as various reports by international organizations, and, interviews from Afghan students studying in Pakistani universities, have been used for this study. Using US-led twenty-year war in Afghanistan, this article shows that in global security governance, under liberal world order, races and civilizations of global South are considered as existential threats to the West which are dealt with policies that contradict rules of liberal world order claimants.